Influence of particle geometry and size on the cell morphology of vacuum assisted rotationally molded foam - Werner, Jannik; Drummer, Dietmar (Cellular Polymers, 2023)
An increased awareness of sustainability among the population leads, from an industrial point of view, to efforts to act more ecologically as well as to the aim for lower production costs and an increased efficiency. With this in mind, a new process has been developed for foaming without blowing agents in rotational molding. Process related air inclusions in the polymer melt are expanded to form the cell structure by means of vacuum application. In the presented study, the influence of different particle sizes as well as the arising potential of deploying microgranules in the otherwise powder-based process is investigated with regard to the resulting foam cells. The results confirm that particle size and form greatly influence the existence and size of air inclusions in the polymer melt. It could be proven that these differences, caused by the particle characteristics, propagate during the foaming process and lead to different cell morphologies in the resultant foam. Furthermore, it is indicated that qualitative predictions of the resulting cell dimensions can be made on the basis of bulk density measurements and the analysis of the sintering behaviour of the initial particle
Keywords: Rotational molding; vacuum assisted rotational foam molding; polymeric foam; physical foaming; vacuum; particle size